Desenvolvimento e caracterização de nanomembranas de poli (fluoreto de vinilideno-co-hexafluorpropileno) (PVDF HFP), dopadas com nanotubo de carbono e aplicadas na atenuação de ruído - Suchilla Garcia Leão (2022)
Multifunctional poly(vinylidene-co-hexafluoropropylene fluoride) (PVDF HFP) nanomembranes doped with carbon nanotube (CNT) were produced using the electrospinning technique. The morphology and acoustic properties of the material were analyzed by different characterization techniques. The images transmitted by Scanning Electron Microscopy (SEM) show a significant decrease in the average diameter of the fibers with the incorporation of CNT, due to the increase in the electrical conductivity of the solution. The Fourier Transform Infrared Spectroscopy (FTIR) technique and the Differential Scanning Calorimetry (DSC) technique were used to evaluate the crystallinity of the samples. The results show that the electrospinning technique can induce the formation of β phase and that the addition of carbon nanotube can also promote the crystallization of this phase as long as it is added in small concentrations. The hydrophobicity of the nanowires was studied from the contact angle formed when applying a drop of water on the surface of the fibers, showing a hydrophobic character for most nanomembranes. PVDF HFP nanomembranes were associated with support materials (airgel or melanin) and the acoustic behavior of the composite material was affected by each of its constituent individuals. The hypothesis of a behavior similar to the Helmholtz resonator caused by the combination of nanomembranes and material support has was confirmed experimentally and by analytical models. The proposed analytical correction of the sound absorption coefficient (α) was able to capture the resonant effect. The aerogel by itself is not an effective sound insulation component, but the nanomembrane + aerogel association can lead to sound absorption coefficients around 0.7 at 6000 Hz frequency. The changes in the frequency of melamine foam from high range (5500 Hz) to mid-range (1600 Hz), with the addition of PVDF HFP nanomembranes, point to the potential for using the composite produced in noise attenuation.